Effect of hardness matching of aero spline sub-materials on wear performance - Xindang He; Tianyu Pan; Suliang Yang; Hongjun Li; Yanru Chen; Jianfeng Xiong (Scientific Reports)
Abstract In engineering applications, wear and tear is a primary contributor to structural vibrations and noise. Excessive wear can lead to adverse effects such as chattering and instability, potentially culminating in catastrophic engineering failures. Thus, enhancing the surface wear resistance of structural components is an urgent necessity to ensure optimal drive train performance. This study investigates the hardness compatibility of commonly used hard spline sub-materials to elucidate the intrinsic damage behavior of these materials. The theoretical framework established here provides a foundation for selecting and optimizing hardness parameters in aerospace spline materials, a critical factor in their effective design. The materials analyzed include 9310 alloy steel, 15-5PH steel, 18CrNiMo, 32Cr3MoVA, and 40CrNiMoA. Results demonstrate that increasing the Hi/He ratio significantly reduces inner spline wear volume, thins the resulting oxide film, and shifts the dominant wear mechanism from abrasive to fatigue wear. The analysis reveals that total wear is minimized when the Hi/He ratio reaches 1.05.